2001
DOI: 10.1590/s0004-282x2001000500004
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcome in 100 patients with aneurysmal subarachnoid hemorrhage

Abstract: -Objective: Clinical and surgical outcome of patients with subarachnoid hemorrhage (SAH) due to ruptured aneurysm were assessed in comparison to pre-operative data and risk factors such as previous medical history, clinical presenting condition, CT findings and site of bleeding. Methods: We evaluated 100 consecutive patients with aneurysmal SAH. Gender, color, history of hypertension, smoking habit, site and size of aneurysm, admittance and before surgery Hunt Hess scale, need for cerebro-spinal fluid shunt, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
1
17
0
2
Order By: Relevance
“…Analysing our results, we found them very similar to these mentioned above and to another in the literature, including a small brazilian series, with 100 patients [10][11][12][13] . Considering the differences in the amount of resorces for health care systems in developed and developing countries, we think were nicely surprised with this results.…”
Section: Discussionsupporting
confidence: 91%
“…Analysing our results, we found them very similar to these mentioned above and to another in the literature, including a small brazilian series, with 100 patients [10][11][12][13] . Considering the differences in the amount of resorces for health care systems in developed and developing countries, we think were nicely surprised with this results.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, periprocedural complications rate was higher than the rates reported in previous studies without focusing on elderly patients only. 11,27,30 Although, we have not analyzed the relation between other factors and periprocedural complications, aneurysm located on and distal the circle of Willis was an independent risk factors of poor outcome, which may be due to relatively smaller diameter of parent artery, longer procedure vascular path, and lead to higher complications rate. What is interesting is that some factors which previously been consider as risk factors included intervention strategies, treatment opportunity, and immediate embolization result were proved have nothing to do with poor clinical outcome.…”
Section: Discussionmentioning
confidence: 93%
“…Not surprisingly, Fisher grade has the most profound influence on 1-year poor outcomes, followed by periprocedural complications and Hunt–Hess grade. 18,27,28 Although, EVT possess many advantages included minimally invasive and have become an important method for aSAH patients, elderly patients frequently present higher periprocedural complications. 24,29 The reasons were that elderly patients generally have tortuous vascular path and worse condition of parent artery due to atherosclerotic stenosis and then prolonged procedural time.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6]9,10,[18][19][20][22][23][24][25][27][28][29][30][31]33,[35][36][37]39,41 Ten studies were excluded because they did not evaluate aneurysm diameter as a risk factor for rehemorrhage rate. 4,6,9,18,22,24,29,36,39,41 Two other articles were excluded because one was a review and the other was an editorial. 25,36 One study was written in Japanese and was thus also excluded.…”
Section: Results Included Studiesmentioning
confidence: 99%